Analisis Literasi Keuangan dan Kebijakan Pemerintah Terhadap Kinerja UMKM di Kota Depok - Elmira Siska; Purwatiningsih Purwatiningsih; Hasanudin Hasanudin; Haliza Nur Ramadina; Desi Marlina (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2024)
MSMEs play a crucial role in the economy. However, the performance of MSMEs is often not optimal due to various challenges, such as limited access to financing, lack of financial literacy, and high dependence on government policies. This study aims to analyze the effect of financial literacy and government policies on the performance of MSMEs in Depok City. A quantitative research design was applied in this study. Primary data were obtained from the results of a questionnaire distributed to 100 selected MSME actors using the accidental sampling method. Data collection was carried out in August - September 2024. Data analysis used the Smart Partial Last Square (PLS) 4 program which includes measuring the outer model and inner model. In testing the outer model, convergent validity, discriminant validity, and composite reliability tests were carried out. In testing the inner model, an evaluation was carried out on multicollinearity, R-squared, goodness of fit, F Square, and path coefficients. The results of the study showed that both financial literacy and government policies had a positive effect on MSME performance, but were not statistically significant. The results of this study imply that financial literacy and government policies need to be improved in terms of implementation and relevance to provide a more tangible impact on MSME performance. Financial literacy programs and policies need to be more tailored to the specific needs of MSMEs and supported by ongoing support to have a significant impact.